High-strength and high-corrosion-resistance magnesium alloy plate and preparation method thereof
By adding Y, Mn and Ca elements to the Mg-Al alloy, and undergoing drastic deformation and low-temperature aging treatment, small twins and dispersed Mg17Al12 phases are formed, which solves the mutually exclusive problems of magnesium alloy strength and corrosion resistance, and realizes a high-strength, high-corrosion-resistant magnesium alloy sheet, suitable for special components.
Patent Information
- Application Number
- CN202510684184.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-07-18
AI Technical Summary
Magnesium alloys have mutually exclusive problems between strength and corrosion resistance, and are difficult to apply in complex and harsh environments.
Based on Mg-Al alloy, a small amount of rare earth Y and Mn elements are added, combined with Ca elements, and a large number of twinning and diffuse second phases are formed through microalloyation and violent deformation treatment. The microstructure is regulated with low-temperature aging treatment.
It significantly improves the mechanical properties and corrosion resistance of magnesium alloys, achieves high strength and uniform corrosion behavior, and is suitable for aerospace, marine ships, automobiles and 3C electronic products.
Smart Images

Figure CN120330558A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesium alloys, and particularly relates to a high-strength and high-corrosion-resistant magnesium alloy sheet and a preparation method thereof. Background Art
[0002] As the lightest structural metal material at present, magnesium alloys have broad application prospects in the fields of aerospace, marine ships, automobiles, 3C electronic products, etc. due to their many advantages such as low density, high specific strength, excellent damping and shock absorption performance, good electromagnetic shielding performance, and biocompatibility. However, due to its active chemical properties, magnesium alloys have the lowest standard electrode potential (-2.37V / SHE) among structural metals, and are extremely prone to galvanic corrosion with other metals or cathodic phases in the matrix, thus significantly deteriorating their corrosion resistance. In addition, kinetically, the PBR (Pilling-Bedworth ratio) of the MgO oxide film on the surface of magnesium alloys is 0.81, which is much less than 1, so it cannot densely cover the surface of magnesium alloys. Moreover, magnesium alloys are extremely prone to local corrosion, resulting in local coverage and non-denseness of the corrosion product Mg(OH)2, thus leading to continuous local corrosion damage of magnesium alloys in the corrosion environment and premature failure of magnesium alloy components. Ultra-pure magnesium without impurities has excellent corrosion resistance (0.25mm / y), but due to the yield strength of pure magnesium being only about 21MPa, it cannot be directly used as a structural component. The addition of a large amount of rare earth elements can significantly improve the mechanical properties of magnesium alloys through strengthening means such as solid solution strengthening and precipitation strengthening, such as GW (Mg-Gd-Y) series alloys. However, while the mechanical properties of magnesium alloys are improved, due to the precipitation of a large number of high-potential second phases and the increase in dislocation density, high-strength magnesium alloys exhibit poor corrosion resistance, thus limiting the application of magnesium alloys in complex and harsh motion scenarios.
[0003] Therefore, how to solve the key problem of the mutual exclusion of the strength and corrosion resistance of magnesium alloys and provide a high-strength and high-corrosion-resistant magnesium alloy is a technical problem that those skilled in the art urgently need to solve. Summary of the Invention
[0004] To solve the above technical problems, the present invention proposes a high-strength and high-corrosion-resistant magnesium alloy sheet and a preparation method and application thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The first aspect of the present invention lies in providing a high-strength and high-corrosion-resistant magnesium alloy sheet, which includes the following components in mass percentage:
[0007] Al 6 - 9%, Y 0.1 - 0.5%, Ca 0.05 - 0.3%, Mn 0.05 - 0.3%, the balance being Mg and unavoidable impurities.
[0008] Beneficial effects: The present invention is based on a low-cost and large-scale applicable Mg-Al alloy system, and at the same time adds a small amount of rare earth Y and Mn elements, which can synergistically reduce the content of Fe impurities in the alloy melt, convert the high-potential Al-Fe phase in the alloy melt into Al-Fe-Y phase and Al-Fe-Mn phase, and further convert it into the low-potential Al-Mn-Y phase, thereby significantly reducing the influence of impurity Fe on the corrosion resistance of the Mg-Al alloy. In addition, the PBR of the oxide Y2O3 of rare earth Y element is 1.13, and combined with Al2O3 (PBR is 1.28), it can significantly make up for the defect that the PBR of MgO on the magnesium surface is less than 1, increase the compactness of the oxide film, and improve the passivation ability of the alloy in the corrosive medium. At the same time, Ca has a low standard electrode potential (-2.87 / SHE), and the addition of Ca in the present invention can segregate around the high-potential Mg 17 Al 12 phase, and convert Mg 17 Al 12 into the low-potential Mg 17 Al 12 (Ca) phase, thereby weakening the galvanic corrosion effect of the Mg 17 Al 12 phase on the magnesium matrix. Secondly, Y and Ca added in the present invention can form Al2Y and Al2Ca hard particles, which can serve as heterogeneous nucleation sites during the solidification of the alloy, accelerate the formation of initial fine grains, significantly refine the grains of the magnesium alloy, and improve the mechanical properties. In addition, the addition of Ca element can improve the flame retardancy and oxidation resistance of the alloy by forming CaO on the surface.
[0009] Preferably, the unavoidable impurities include one or any several of Fe, Ni, Cu, and Si, and the total content of the impurities is less than 0.08%.
[0010] Optionally, the high-strength and high-corrosion-resistant magnesium alloy sheet includes the following raw materials:
[0011] Pure magnesium ingot, pure aluminum ingot, Mg-Y master alloy, Mg-Ca master alloy, and Mn source.
[0012] Preferably, the Mn source includes Mg-Mn master alloy or anhydrous manganese chloride.
[0013] The second aspect of the present invention lies in providing a preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet, including the following steps:
[0014] The magnesium alloy ingot is homogenized and then extruded into shape. The obtained extruded sheet is then subjected to rolling and low-temperature aging treatment to obtain the high-strength and high-corrosion-resistant magnesium alloy sheet.
[0015] Beneficial effects: Through the deformation treatment process of conventional extrusion treatment plus single-pass rolling, the grain size of the magnesium alloy can be significantly reduced, and the mechanical properties of the alloy can be significantly improved through fine grain strengthening. At the same time, a large number of nano-twins and strong basal texture generated during the rolling process can also improve the mechanical strength of the alloy, and the presence of the strong basal texture can improve the corrosion resistance of the alloy sheet. Further, a large number of fine and dispersed Mg 17 Al 12 phases precipitated by the low-temperature aging treatment of the rolled sheet can promote the uniform corrosion of the magnesium matrix and the formation of a uniform and dense corrosion product film, thereby significantly improving the corrosion resistance of the alloy. Compared with the coarse Mg 17 Al 12 phases in the traditional AZ91 alloy, the fine and dispersed Mg 17 Al 12 phases have a weaker micro-galvanic effect. Therefore, compared with the severe local corrosion of the traditional commercial AZ91 alloy, the alloy of the present invention shows uniform corrosion behavior, which is more conducive to the formation of a uniform corrosion product film and the improvement of corrosion resistance.
[0016] Preferably, the homogenization treatment temperature is 350 - 400 °C and the time is 12 - 24 hours.
[0017] Beneficial effects: For Mg-Al series alloys, too low a temperature will not cause the Mg 17 Al 12 phase to dissolve into the magnesium matrix, while the melting point of Mg 17 Al 12 is about 440 °C, and too high a temperature will cause the Mg 17 Al 12 phase to melt. Therefore, the homogenization temperature selected in the present invention is 350 - 400 °C. And a treatment time shorter than the above will result in poor homogenization treatment effect and affect the subsequent microstructure; a treatment time longer than the above will result in coarse grains and affect the subsequent mechanical properties of the alloy.
[0018] Preferably, the temperature of the extrusion forming is 350 - 390 °C, the speed is 1 - 1.5 m / min, and the extrusion ratio is 10:1 - 30:1.
[0019] Preferably, the rolling is single-pass rolling, the temperature of the rolling is 275 - 350 °C, the speed is 350 - 400 r / min, and the reduction per pass of the single-pass rolling is 12 - 20% of the thickness of the extruded sheet.
[0020] Beneficial effects: Single-pass rolling has the potential for simple and scalable application. A lower rolling temperature can significantly improve the mechanical properties of the alloy. However, if the reduction per pass in single-pass rolling is too high, the sheet is prone to cracking. Therefore, the reduction per pass is 12 - 20%.
[0021] Preferably, the temperature of the low-temperature aging treatment is 175 - 200 °C, and the time is 8 - 16 hours.
[0022] Beneficial effects: Under the above low-temperature aging treatment conditions, the recovery of dislocations and the recrystallization of grains can be weakened, avoiding the decline in mechanical properties. At the same time, long-term aging treatment can precipitate fine and dispersed Mg 17 Al 12 phase, promoting the uniform corrosion of the alloy and improving the corrosion resistance of the alloy.
[0023] Optionally, the preparation method of the magnesium alloy ingot includes the following steps:
[0024] Weigh raw materials of pure magnesium ingot, pure aluminum ingot, Mg-Y master alloy, Mg-Ca master alloy, and Mn source. Under a protective atmosphere, preheat the raw materials and then melt them, followed by refining, stirring, standing, skimming, and casting to obtain a magnesium alloy ingot.
[0025] Among them, the purpose of the preheating is to remove the moisture in the raw materials.
[0026] Preferably, the protective atmosphere is a mixed gas atmosphere of SF6 and CO2, where the volume ratio of SF6 to CO2 is 9:1.
[0027] Preferably, the melting includes the following steps:
[0028] Under the protection of a mixed gas of SF6 and CO2, melt the pure magnesium ingot at 690 °C, then add the Mn source between 700 - 710 °C. After complete melting, stir for 3 - 5 minutes, then add the pure aluminum ingot at 710 - 720 °C, and keep warm for 10 - 20 minutes until the aluminum ingot melts. Remove the slag on the surface of the melt, add Mg-Y and Mg-Ca master alloys in the range of 750 - 760 °C, and keep warm for 10 - 20 minutes until the master alloys are completely melted to obtain a magnesium alloy melt.
[0029] Preferably, the temperature of the refining is 740 - 750 °C, and the time is 5 - 10 minutes.
[0030] Preferably, the refining agent used in the refining process includes raw materials with the following mass fractions: KCl 49 wt%, CaCl2 24 wt%, BaCl2 14 wt%, CaF2 6 wt%, YCl3 7 wt%.
[0031] Preferably, the static setting is as follows: first, statically set at 740 - 750 °C for 30 - 40 minutes, and then cool down to 710 - 720 °C and statically set for 20 - 30 minutes for iron reduction treatment.
[0032] Preferably, the casting temperature is 690 - 710 °C.
[0033] The third aspect of the present invention lies in providing an application of a high-strength and high-corrosion-resistant magnesium alloy sheet in aerospace, marine ships, automobiles, and / or 3C electronic products.
[0034] Beneficial effects: Since the alloy prepared by the present invention exhibits excellent mechanical properties while also showing uniform corrosion behavior, it is more conducive to the formation of a uniform corrosion product film and the improvement of corrosion resistance. These properties are beneficial for its wide application in special component materials of aerospace, marine ships, automobiles, and / or 3C electronic products.
[0035] Compared with the prior art, the present invention has the following advantages and technical effects:
[0036] Starting from two aspects of microalloying and promoting the formation of a large number of twins and low-potential second phases, the present invention uses a small amount of Y, Ca, and Mn elements for microalloying to improve the corrosion resistance of the alloy, and further regulates the microstructure through severe deformation treatment and post-aging treatment to form a large number of twins and dispersed second phases, realizing a substantial improvement in the mechanical and corrosion resistance of the alloy. The deformation process in the present invention is conventional extrusion and single-pass rolling treatment, which has the advantage of simple process, can be mass-produced, and has the prospect of large-scale commercial application with low cost. In addition, the alloy sheet of the present invention can be applied in lightweight demand fields such as 3C digital products and new energy vehicles. Description of the Drawings
[0037] The drawings constituting a part of this application are used to provide a further understanding of this application. The schematic embodiments and descriptions thereof of this application are used to explain this application and do not constitute an improper limitation to this application. In the drawings:
[0038] Figure 1 It is the optical micrograph of the high-strength and corrosion-resistant Mg-8Al-0.3Y-0.2Ca-0.2Mn alloy in Example 1;
[0039] Figure 2 It is the optical micrograph of the Mg-8Al-0.3Y-0.2Ca-0.2Mn alloy without low-temperature aging treatment in Comparative Example 1;
[0040] Figure 3 It is the SEM micrograph of the microstructure of the high-strength and corrosion-resistant Mg-8Al-0.3Y-0.2Ca-0.2Mn alloy in Example 1;
[0041] Figure 4 SEM micrograph of the microstructure of the as-extruded Mg-8Al-0.3Y-0.2Ca-0.2Mn alloy without rolling and low-temperature aging treatment in Comparative Example 5;
[0042] Figure 5 EBSD inverse pole figure of the high-strength and corrosion-resistant Mg-8Al-0.3Y-0.2Ca-0.2Mn alloy in Example 1;
[0043] Figure 6 EBSD inverse pole figure of the as-extruded Mg-8Al-0.3Y-0.2Ca-0.2Mn alloy without rolling and low-temperature aging treatment in Comparative Example 5;
[0044] Figure 7 Cross-sectional corrosion morphology of the high-strength and corrosion-resistant Mg-8Al-0.3Y-0.2Ca-0.2Mn alloy in Example 1 after being immersed in the corrosion medium for 7 days;
[0045] Figure 8 Cross-sectional corrosion morphology of the low-corrosion-resistant Mg-8Al-0.2Mn alloy in Comparative Example 2 after being immersed in the corrosion medium for 7 days. Detailed implementation manners
[0046] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0047] To make the above objects, features, and advantages of the present invention more obvious and understandable, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation manners.
[0048] Unless otherwise specified, room temperature or normal temperature in the embodiments of the present invention both refer to 25 ± 3°C.
[0049] Unless otherwise specified, the raw materials in the embodiments of the present invention are all obtained through commercial channels;
[0050] Among them, the Mg content in the pure magnesium ingot is 99.95 wt%.
[0051] The Al content in the pure aluminum ingot is 99.99 wt%.
[0052] The Mg content in the Mg-Y master alloy is 70 wt%, and the Y content is 30 wt%;
[0053] The Mg content in the Mg-Ca master alloy is 70 wt%, and the Ca content is 30 wt%.
[0054] The refining agent is obtained by mixing raw materials with the following mass fractions: 49 wt% of KCl, 24 wt% of CaCl₂, 14 wt% of BaCl₂, 6 wt% of CaF, and 7 wt% of YCl₃;
[0055] The addition amount of the refining agent is 1.5% of the total mass of the magnesium alloy sheet raw materials.
[0056] Example 1
[0057] A preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet. The magnesium alloy is Mg-8Al-0.3Y-0.2Ca-0.2Mn, and the method includes the following steps:
[0058] (1) By mass percentage, according to the alloy composition of Al: 8%, Y: 0.3%, Ca: 0.2%, Mn: 0.2%, unavoidable impurity elements less than 0.08%, and the balance being Mg, the corresponding pure magnesium ingots, pure aluminum ingots, Mg-Y, Mg-Ca master alloys, and anhydrous manganese chloride are weighed and preheated to remove moisture.
[0059] (2) Under the protection of a mixed gas of SF₆ and CO₂ (the volume ratio of SF₆ to CO₂ is 9:1), the pure magnesium ingot is melted at 690 °C, then anhydrous manganese chloride is added between 710 °C while stirring for 5 minutes. The pure aluminum ingot is added at about 720 °C, and then held for 20 minutes until the aluminum ingot melts. The slag on the surface of the melt is removed, and the Mg-Y and Mg-Ca master alloys are added within the range of 750 °C and held for 20 minutes to obtain a magnesium alloy melt.
[0060] (3) Under the protection of a mixed gas of SF₆ and CO₂, the magnesium alloy melt is mixed with the refining agent and then refined at 750 °C, stirred vigorously for 10 minutes, then held statically at 750 °C for 40 minutes, and finally cooled to 710 °C and held statically for 30 minutes for iron reduction treatment to obtain a purified magnesium alloy melt. Then the furnace temperature is reduced to 690 °C, the slag on the surface of the purified magnesium alloy melt is removed, and it is cast into a preheated metal mold to obtain a magnesium alloy ingot.
[0061] (4) The above magnesium alloy ingot is subjected to homogenization treatment at a temperature of 390 °C for 24 hours, and then the homogenized ingot is extruded into a sheet at 350 °C to obtain an extruded sheet. Among them, the extrusion ratio is 15:1, and the extrusion speed is 1.5 m / min.
[0062] (5) The above extruded sheet is subjected to single-pass rolling treatment at 275 °C, and the rolling speed is 350 r / min. The initial thickness of the extruded sheet is 7 mm, and the reduction per pass is 12%. A magnesium alloy rolled sheet is obtained, and then low-temperature aging treatment is carried out. The aging temperature is 200 °C, and the aging time is 12 hours to obtain a high-strength and high-corrosion-resistant magnesium alloy sheet. Its mechanical properties and corrosion properties are shown in Table 1.
[0063] After testing, the chemical composition of the magnesium alloy obtained by the preparation method of this example is as follows: Al 8.10 wt%, Y 0.28 wt%, Ca 0.15 wt%, Mn 0.13 wt%. The inevitable impurities include: Fe 0.0048 wt%, Ni 0.0010 wt%, Cu 0.0008 wt%, Si 0.03 wt%, and the balance is Mg (the difference between the product element composition and the design target is an acceptable error).
[0064] Example 2
[0065] A preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet. The magnesium alloy is Mg-8Al-0.1Y-0.1Ca-0.1Mn, and the method includes the following steps:
[0066] (1) By mass percentage, according to Al: 8%, Y: 0.1%, Ca: 0.1%, Mn: 0.1%. The inevitable impurity elements are less than 0.06%, and the balance is Mg. Weigh the corresponding pure magnesium ingot, pure aluminum ingot, Mg-Y, Mg-Ca, and Mg-Mn master alloys, and carry out preheating treatment to remove moisture.
[0067] (2) Under the protection of a mixed gas of SF6 and CO2 (the volume ratio of SF6 and CO2 is 9:1), the pure magnesium ingot is melted at 690 °C, and then the Mg-Mn master alloy is added between 710 °C. After the alloy is completely melted, it is stirred for 5 minutes. The pure aluminum ingot is added within the range of 720 °C, and then it is held for 20 minutes until the aluminum ingot melts. The slag on the surface of the melt is removed. The Mg-Y and Mg-Ca master alloys are added within the range of 760 °C and held for 20 minutes to obtain a magnesium alloy melt.
[0068] (3) Under the protection of a mixed gas of SF6 and CO2, the magnesium alloy melt is mixed with a refining agent and refined at 750 °C, stirred vigorously for 10 minutes, then held at 750 °C for 40 minutes, and finally cooled to 710 °C and held for 30 minutes for iron reduction treatment to obtain a purified magnesium alloy melt. Then the furnace temperature is reduced to 690 °C, the slag on the surface of the above purified magnesium alloy melt is removed, and it is poured into a preheated metal mold to obtain a magnesium alloy ingot.
[0069] (4) The above magnesium alloy ingot is subjected to homogenization treatment at a temperature of 390 °C for 24 hours, and then the homogenized ingot is extruded into a sheet at 350 °C to obtain an extruded sheet. Among them, the extrusion ratio is 15:1 and the extrusion speed is 1.5 m / min.
[0070] (5) The above extruded sheet is subjected to single-pass rolling treatment at 275 °C, and the rolling speed is 350 r / min. The initial thickness of the extruded sheet is 7 mm, and the reduction per pass of single-pass rolling is 15%, obtaining a magnesium alloy rolled sheet, and then low-temperature aging treatment is carried out. The aging temperature is 175 °C and the aging time is 16 hours, obtaining a high-strength and high-corrosion-resistant magnesium alloy sheet. Its mechanical properties and corrosion properties are shown in Table 1.
[0071] After testing, the chemical composition of the magnesium alloy in this example is as follows: Al 7.95 wt%, Y 0.12 wt%, Ca 0.11 wt%, Mn 0.10 wt%. The inevitable impurities include: Fe 0.0054 wt%, Ni 0.0011 wt%, Cu 0.0006 wt%, Si 0.036 wt%, and the balance is Mg.
[0072] Example 3
[0073] A method for preparing a high-strength and high-corrosion-resistant magnesium alloy sheet. The magnesium alloy is Mg-8Al-0.5Y-0.2Ca-0.2Mn, and the method includes the following steps:
[0074] (1) By mass percentage, according to Al: 8%, Y: 0.5%, Ca: 0.2%, Mn: 0.2%. The inevitable impurity elements are less than 0.08%, and the balance is Mg. Weigh the corresponding pure magnesium ingot, pure aluminum ingot, Mg-Y and Mg-Ca master alloys, and anhydrous manganese chloride, and carry out preheating treatment to remove moisture.
[0075] (2) Under the protection of a mixed gas of SF6 and CO2 (the volume ratio of SF6 and CO2 is 9:1), the pure magnesium ingot is melted at 690 °C, and then anhydrous manganese chloride is added between 710 °C while stirring for 5 minutes. The pure aluminum ingot is added within the range of 720 °C, and then held for 20 minutes until the aluminum ingot melts. The slag on the surface of the melt is removed, and the Mg-Y and Mg-Ca master alloys are added within the range of 760 °C and held for 20 minutes to obtain a magnesium alloy melt.
[0076] (3) Under the protection of the SF6 and CO2 mixed gas, the magnesium alloy melt is mixed with a refining agent and then refined at 750 °C, stirred vigorously for 10 minutes, then kept standing and heat-insulated at 750 °C for 40 minutes, and finally cooled to 710 °C and kept standing for 30 minutes for iron reduction treatment to obtain a purified magnesium alloy melt. Then, the furnace temperature is reduced to 700 °C, the slag on the surface of the above purified magnesium alloy melt is skimmed off, and then it is cast into a preheated metal mold to obtain a magnesium alloy ingot.
[0077] (4) The above magnesium alloy ingot is subjected to homogenization treatment at a temperature of 390 °C for 24 hours, and then the homogenized ingot is extruded into a sheet at 350 °C to obtain an extruded sheet, wherein the extrusion ratio is 15:1 and the extrusion speed is 1.5 m / min.
[0078] (5) The above extruded sheet is subjected to single-pass rolling treatment at 275 °C, and the rolling speed is 350 r / min. The initial thickness of the extruded sheet is 7 mm, and the reduction per pass is 15%. A magnesium alloy rolled sheet is obtained, and then low-temperature aging treatment is carried out. The aging temperature is 200 °C and the aging time is 16 hours to obtain a high-strength and high-corrosion-resistant magnesium alloy sheet, and its mechanical properties and corrosion properties are shown in Table 1.
[0079] After testing, the chemical composition of the magnesium alloy in this example is as follows: Al 8.06 wt%, Y 0.48 wt%, Ca 0.17 wt%, Mn 0.16 wt%, and the inevitable impurities include: Fe 0.0042 wt%, Ni 0.0008 wt%, Cu 0.0005 wt%, Si 0.038 wt%, and the balance is Mg.
[0080] Example 4
[0081] A preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet, the magnesium alloy being Mg-8Al-0.2Y-0.15Ca-0.15Mn, comprising the following steps:
[0082] (1) By mass percentage, according to Al: 8%, Y: 0.2%, Ca: 0.15%, Mn: 0.15%. The inevitable impurity elements are less than 0.06%, and the balance is Mg. Weigh the corresponding pure magnesium ingot, pure aluminum ingot, Mg-Y and Mg-Ca master alloys, and anhydrous manganese chloride, and carry out preheating treatment to remove moisture.
[0083] (2) Under the protection of a mixed gas of SF6 and CO2 (the volume ratio of SF6 to CO2 is 9:1), pure magnesium ingots are melted at 690 °C, and then anhydrous manganese chloride is added between 710 °C while stirring for 5 minutes. Pure aluminum ingots are added within the range of 720 °C, and then kept warm for 20 minutes until the aluminum ingots melt. The slag on the surface of the melt is removed, and Mg-Y and Mg-Ca master alloys are added within the range of 760 °C and kept warm for 20 minutes to obtain a magnesium alloy melt.
[0084] (3) Under the protection of a mixed gas of SF6 and CO2, the magnesium alloy melt is mixed with a refining agent and then refined at 750 °C with vigorous stirring for 10 minutes, then kept static and warm at 750 °C for 40 minutes, and finally cooled to 710 °C and kept static for 30 minutes for iron reduction treatment to obtain a purified magnesium alloy melt. Then the furnace temperature is reduced to 700 °C, the slag on the surface of the purified magnesium alloy melt is removed, and it is poured into a preheated metal mold to obtain a magnesium alloy ingot.
[0085] (4) The above magnesium alloy ingot is subjected to homogenization treatment at a temperature of 390 °C for 24 hours, and then the homogenized ingot is extruded into a sheet at 350 °C to obtain an extruded sheet, where the extrusion ratio is 15:1 and the extrusion speed is 1.5 m / min.
[0086] (5) The above extruded sheet is subjected to single-pass rolling treatment at 285 °C, and the rolling speed is 350 r / min. The initial thickness of the extruded sheet is 10 mm, and the reduction per pass of single-pass rolling is 20% to obtain a magnesium alloy rolled sheet, and then it is subjected to low-temperature aging treatment at an aging temperature of 175 °C for 16 hours to obtain a high-strength and high-corrosion-resistant magnesium alloy sheet, and its mechanical properties and corrosion properties are shown in Table 1.
[0087] After testing, the chemical composition of the magnesium alloy in this example is as follows: Al 7.96 wt%, Y 0.18 wt%, Ca 0.12 wt%, Mn 0.14 wt%, and inevitable impurities include: Fe 0.0055 wt%, Ni 0.0007 wt%, Cu 0.00010 wt%, Si 0.042 wt%, and the balance is Mg.
[0088] Comparative Example 1
[0089] A method for preparing a high-strength and high-corrosion-resistant magnesium alloy sheet, the magnesium alloy being Mg-8Al-0.3Y-0.2Ca-0.2Mn, comprising the following steps:
[0090] (1) By mass percentage, according to Al: 8%, Y: 0.3%, Ca: 0.2%, Mn: 0.2%. The inevitable impurity elements are less than 0.06%, and the balance is Mg. Weigh the corresponding pure magnesium ingots, pure aluminum ingots, Mg-Y and Mg-Ca master alloys, and anhydrous manganese chloride, and perform preheating treatment to remove moisture.
[0091] (2) Under the protection of a mixed gas of SF6 and CO2 (the volume ratio of SF6 to CO2 is 9:1), melt the pure magnesium ingot at 690 °C, then add anhydrous manganese chloride between 710 °C while stirring for 5 minutes. Add the pure aluminum ingot within the range of 720 °C, and then keep it warm for 20 minutes until the aluminum ingot melts. Remove the slag on the surface of the melt, add Mg-Y and Mg-Ca master alloys within the range of 760 °C, and keep it warm for 20 minutes to obtain a magnesium alloy melt.
[0092] (3) Under the protection of a mixed gas of SF6 and CO2, mix the magnesium alloy melt with a refining agent and refine it at 750 °C, stir vigorously for 10 minutes, then keep it static and warm at 750 °C for 40 minutes, and finally cool down to 710 °C and keep it static for 30 minutes for iron reduction treatment to obtain a purified magnesium alloy melt. Then lower the furnace temperature to 700 °C, remove the slag on the surface of the purified magnesium alloy melt, and then pour it into a preheated metal mold to obtain a magnesium alloy ingot.
[0093] (4) Perform homogenization treatment on the above magnesium alloy ingot at a homogenization temperature of 390 °C for 24 hours, and then extrude the homogenized ingot into a sheet at 350 °C to obtain an extruded sheet. Among them, the extrusion ratio is 15:1, and the extrusion speed is 1.5 m / min.
[0094] (5) Perform single-pass rolling treatment on the above extruded sheet at 275 °C, and the rolling speed is 350 r / min. The initial thickness of the extruded sheet is 7 mm, and the reduction per pass is 12% to obtain a magnesium alloy rolled sheet, and its mechanical properties and corrosion properties are shown in Table 1.
[0095] After testing, the chemical composition of the magnesium alloy in this example is as follows: Al 8.10 wt%, Y 0.28 wt%, Ca 0.15 wt%, Mn 0.13 wt%, and the inevitable impurities include: Fe 0.0048 wt%, Ni 0.0010 wt%, Cu 0.0008 wt%, Si 0.03 wt%, and the balance is Mg.
[0096] Comparative Example 2
[0097] A method for preparing a magnesium alloy sheet, the magnesium alloy is Mg-8Al-0.2Mn, and it includes the following steps:
[0098] (1) By mass percentage, according to Al: 8%, Mn: 0.2%. The inevitable impurity elements are less than 0.06%, and the balance is Mg. Weigh the corresponding pure magnesium ingots, pure aluminum ingots, and anhydrous manganese chloride, and perform preheating treatment to remove moisture.
[0099] (2) Under the protection of a mixed gas of SF6 and CO2 (the volume ratio of SF6 and CO2 is 9:1), melt the pure magnesium ingot at 690 °C, then add anhydrous manganese chloride between 710 °C while stirring for 5 minutes. Add the pure aluminum ingot within the range of 720 °C, and then keep it warm for 20 minutes until the aluminum ingot melts to obtain a magnesium alloy melt.
[0100] (3) Under the protection of a mixed gas of SF6 and CO2, mix the magnesium alloy melt with a refining agent and refine it at 750 °C, stir vigorously for 10 minutes, then keep it static and warm at 750 °C for 40 minutes, and finally cool it down to 710 °C and keep it static for 30 minutes for iron reduction treatment to obtain a purified magnesium alloy melt. Then lower the furnace temperature to 700 °C, skim off the slag on the surface of the purified magnesium alloy melt, and then pour it into a preheated metal mold to obtain a magnesium alloy ingot.
[0101] (4) Perform homogenization treatment on the above magnesium alloy ingot. The homogenization treatment temperature is 390 °C, and the treatment time is 24 hours. Then extrude the homogenized ingot into a sheet at 350 °C to obtain an extruded sheet. Among them, the extrusion ratio is 15:1, and the extrusion speed is 1.5 m / min.
[0102] (5) Perform single-pass rolling treatment on the above extruded sheet at 275 °C. The rolling speed is 350 r / min. The initial thickness of the extruded sheet is 7 mm, and the reduction per pass is 12%. Then perform low-temperature aging treatment. The aging temperature is 175 °C, and the aging time is 12 hours to obtain a magnesium alloy sheet. Its mechanical properties and corrosion properties are shown in Table 1.
[0103] After testing, the chemical composition of the magnesium alloy in this comparative example is as follows: Al 8.15 wt%, Mn 0.21 wt%, inevitable impurities include: Fe 0.0075 wt%, Ni 0.00010 wt%, Cu 0.0012 wt%, Si 0.05 wt%, and the balance is Mg.
[0104] Comparative Example 3
[0105] A preparation method of a magnesium alloy sheet, which uses a commercial AZ80 magnesium alloy for rolling treatment. The chemical composition of the magnesium alloy includes: Al 8.13 wt%, Zn 0.46 wt%, Mn 0.25 wt%, Fe 0.0068 wt%, Ni 0.0010 wt%, Cu 0.0012 wt%, Si 0.043 wt%, and the balance is Mg. The specific rolling method includes the following steps:
[0106] (1) Homogenize the AZ80 magnesium alloy ingot at 390 °C for 24 hours, and then extrude the homogenized ingot into a sheet at 350 °C. Among them, the extrusion ratio is 15:1, and the extrusion speed is 1.5 m / min to obtain an extruded sheet.
[0107] (2) Perform single-pass rolling treatment on the above extruded sheet at 275 °C. The rolling speed is 350 r / min, the initial thickness of the extruded sheet is 7 mm, and the reduction per pass is 12% to obtain an AZ80 magnesium alloy rolled sheet. Its mechanical properties and corrosion resistance are shown in Table 1.
[0108] Comparative Example 4
[0109] A preparation method of a magnesium alloy sheet, which is only different from Example 1 in that: the magnesium alloy is Mg-8Al-1Y-0.2Ca-0.2Mn, and includes the following components by mass percentage: Al: 8%, Y: 1%, Ca: 0.2%, Mn: 0.2%, unavoidable impurity elements are less than 0.06%, and the balance is Mg. Other process steps and parameters are the same as those in Example 1.
[0110] The chemical composition of the obtained magnesium alloy is as follows: Al 8.02 wt%, Y 0.95 wt%, Ca 0.16 wt%, Mn 0.17 wt%. Unavoidable impurities include: Fe 0.0053 wt%, Ni 0.0006 wt%, Cu 0.0012 wt%, Si 0.039 wt%, and the balance is Mg. Its mechanical properties and corrosion resistance are shown in Table 1.
[0111] Comparative Example 5
[0112] A preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet. The magnesium alloy is Mg-8Al-0.3Y-0.2Ca-0.2Mn, and includes the following steps:
[0113] (1) By mass percentage, weigh the corresponding pure magnesium ingots, pure aluminum ingots, Mg-Y, Mg-Ca master alloys, and anhydrous manganese chloride according to the alloy composition of Al: 8%, Y: 0.3%, Ca: 0.2%, Mn: 0.2%, unavoidable impurity elements less than 0.06%, and the balance is Mg, and perform preheating treatment to remove moisture.
[0114] (2) Under the protection of a mixed gas of SF6 and CO2 (the volume ratio of SF6 to CO2 is 9:1), pure magnesium ingots are melted at 690 °C, and then anhydrous manganese chloride is added between 710 °C. While adding, stir for 5 minutes. Pure aluminum ingots are added within the range of 720 °C, and then keep warm for 20 minutes until the aluminum ingots melt. Remove the slag on the surface of the melt, add Mg-Y and Mg-Ca master alloys within the range of 760 °C, and keep warm for 20 minutes to obtain a magnesium alloy melt.
[0115] (3) Under the protection of a mixed gas of SF6 and CO2, refining is carried out at 750 °C, stirring vigorously for 10 minutes, then standing and keeping warm at 750 °C for 40 minutes, and finally cooling down to 710 °C and standing for 30 minutes for iron reduction treatment to obtain a purified magnesium alloy melt. Then, the furnace temperature is reduced to 690 °C, the slag on the surface of the purified magnesium alloy melt is removed, and then it is cast into a preheated metal mold to obtain a magnesium alloy ingot.
[0116] (4) The above-mentioned magnesium alloy ingots are subjected to homogenization treatment at a temperature of 390 °C for 24 hours, and then the homogenized ingots are extruded into plates at 350 °C to obtain extruded plates. Among them, the extrusion ratio is 15:1, and the extrusion speed is 1.5 m / min.
[0117] The chemical composition of the obtained magnesium alloy is as follows: Al 8.10 wt%, Y 0.28 wt%, Ca 0.15 wt%, Mn 0.13 wt%. Inevitable impurities include: Fe 0.0048 wt%, Ni 0.0010 wt%, Cu 0.0008 wt%, Si 0.03 wt%, and the balance is Mg. Its mechanical properties and corrosion properties are shown in Table 1.
[0118] Technical effects:
[0119] 1. Mechanical property and corrosion property tests:
[0120] For the mechanical property test, the gauge size of the tensile sheet is 25×6×2 mm, with three parallel specimens. The tensile test standard complies with the national standard GB / T 228.1-2021. The corrosion test solution is a neutral 3.5 wt% NaCl solution, the test temperature is room temperature 25 °C, the sample size is 20×20×5 mm, and the test time is 7 days. The immersion corrosion test complies with the national standard GB 10124-88, and the weight loss rate is calculated by calculating the weight difference between the sample before the corrosion test and the sample after cleaning the corrosion test. Among them, the weight loss rate (mg / cm 2( / day) is equal to the weight difference divided by the specimen surface area divided by the number of test days, and can be converted into the average depth corrosion rate (mm / year) through formula conversion. The hydrogen evolution test device built simply is used to record the reduction of the solution in the burette to equivalently represent the volume of hydrogen gas precipitated by magnesium corrosion. The hydrogen evolution rate (mL / cm 2 / day) is obtained by dividing the volume of hydrogen gas precipitated by the specimen surface area divided by the number of test days. The corrosion cleaning agent is 200 g / L CrO3 + 10 g / L AgNO3, which is a common cleaning method for magnesium alloy corrosion products and complies with the national standard GB / T 16545-2015. The test results of the mechanical properties and weight loss hydrogen evolution rate of each group of magnesium alloys are shown in Table 1.
[0121] Table 1 Test results of mechanical properties and corrosion properties of magnesium alloys in the examples and comparative examples
[0122]
[0123] As can be seen from Table 1, the magnesium alloys obtained in Examples 1-4 of the present invention have a good combination of high strength and low corrosion rate, and their corrosion rate is much lower than the corrosion rate of 0.25 mm / y of ultra-pure magnesium reported by Cao et al. in the article "Corrosion of ultra-high-purity Mg in 3.5% NaCl solution saturated with Mg(OH)2", and this corrosion rate is considered to be the intrinsic corrosion rate of magnesium. From the comparison between Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 without low-temperature aging treatment shows the highest yield and tensile strength, but its corrosion resistance is significantly lower than that of the alloy in Example 1 with low-temperature aging treatment. This is because a large number of fine Mg 17 Al 12 phases are precipitated in the Mg-Al-Y-Ca-Mn rolled sheet after low-temperature aging treatment, and its optical microstructure is as shown in Figure 1 , and the SEM microstructure is as shown in Figure 3 . From Figure 1 and Figure 3 , it can be seen that a large number of fine Mg 17 Al 12 phases are precipitated at the twins in the alloy of Example 1. The existence of the dispersed Mg 17 Al 12 phase can promote the uniform corrosion of the magnesium matrix and promote the rapid formation of a uniform corrosion product film on the matrix, thereby significantly improving the corrosion resistance of the magnesium alloy. Figure 2 is the Mg-Al-Y-Ca-Mn rolled sheet without low-temperature aging in Comparative Example 1, and its high strength is attributed to the high dislocation density and a large number of twin structures.
[0124] Figure 4SEM microstructure of the extruded Mg-Al-Y-Ca-Mn alloy in Comparative Example 5. It can be seen that the extruded alloy without rolling treatment does not show twinned structures, but rather some relatively large Mg 17 Al 12 network structures. As can be seen from Table 1, the mechanical strength and corrosion resistance of the alloy in Comparative Example 5 are much lower than those of the Mg-Al-Y-Ca-Mn alloy subjected to rolling and low-temperature aging treatment in Example 1. Low-temperature rolling treatment causes a large number of fine twinned structures to form in the Mg-Al-Y-Ca-Mn alloy and simultaneously refines the grain size. Its EBSD inverse pole figure is as shown in Figure 5 . It can be seen that low-temperature rolling treatment significantly refines the grain size of the Mg-Al-Y-Ca-Mn alloy and generates a large number of twinned structures. Compared with the grain size of the extruded state ([[]] Figure 6 ), the grain size (d) of the rolled alloy decreases from 27 μm to 19 μm, thus significantly improving the mechanical strength of the rolled alloy. At the same time, a large number of low-energy twinned structures do not reduce the corrosion resistance of the alloy. Through the formation of a large number of twins and the presence of dispersed Mg 17 Al 12 phases, the mechanical strength and corrosion resistance of the Mg-Al-Y-Ca-Mn alloy are synergistically improved to a large extent.
[0125] Figure 7 is the corrosion cross-sectional morphology of Example 1 after immersion in 3.5 wt% NaCl solution for 7 days. It can be seen that the rolled and aged alloy with dispersed Mg 17 Al 12 phases shows uniform corrosion behavior. A dense corrosion product film uniformly covers the surface of the magnesium matrix, effectively blocking the rapid expansion of magnesium matrix corrosion. Figure 8 is the corrosion cross-sectional morphology of the unalloyed rolled and aged Mg-Al-Mn alloy in Comparative Example 2 after immersion in 3.5 wt% NaCl solution for 7 days. As can be seen from the figure, the Mg-Al-Mn alloy shows typical local corrosion behavior, and the corrosion pit depth is about 100 - 200 μm. As can be seen from Table 1, the corrosion rate of the magnesium alloy obtained in Comparative Example 1 is 118 times that of Example 1, showing an astonishing corrosion rate. It can be seen that the addition of a small amount of Y and Ca elements in the present invention significantly improves the corrosion resistance of the alloy, which is attributed to the purification effect of Y on impurities and the effect of stabilizing the passive film. In addition, the addition of Y can transform the high-potential Al-Mn phase into the low-potential Al-Mn-Y phase, thereby weakening the galvanic corrosion effect on the magnesium matrix. The addition of a small amount of Ca can transform the Mg 17 Al 12 phase into the lower-potential Mg 17 Al 12 (Ca) phase, thereby further reducing the galvanic corrosion of the matrix.
[0126] In summary, through the microalloying of Y, Ca, and Mn elements in the present invention, and through post-extrusion rolling and low-temperature aging treatment, a Mg-Al-Y-Ca-Mn alloy with a large number of fine twins and dispersed Mg 17 Al 12 phase is obtained, achieving a synergistic improvement in the mechanical strength and corrosion resistance of the alloy. The high-strength and high-corrosion-resistant magnesium alloy sheet provided by the present invention has great application prospects in the fields of 3C digital products and new energy vehicles that require lightweighting.
[0127] The above is only a preferred specific embodiment of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed in the present application should be covered by the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. A high-strength and highly corrosion-resistant magnesium alloy sheet, characterized in that, Comprising the following components by mass percentage: Al 6 - 9%, Y 0.1 - 0.5%, Ca 0.05 - 0.3%, Mn 0.05 - 0.3%, the balance being Mg and inevitable impurities.
2. The preparation method of a high-strength and highly corrosion-resistant magnesium alloy sheet according to claim 1, characterized in that, Comprising the following steps: The magnesium alloy ingot is homogenized and then extruded. The obtained extruded sheet is then subjected to rolling and low - temperature aging treatment to obtain the high - strength and high - corrosion - resistant magnesium alloy sheet.
3. The preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet according to claim 2, characterized in that, The temperature of the homogenization treatment is 350 - 400 °C and the time is 12 - 24 hours.
4. The preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet according to claim 2, characterized in that, The temperature of the extrusion is 350 - 390 °C, the speed is 1 - 1.5 m / min, and the extrusion ratio is (10 - 30):
1.
5. The preparation method of a high-strength and highly corrosion-resistant magnesium alloy sheet according to claim 2, characterized in that, The rolling is single - pass rolling. The temperature of the rolling is 275 - 350 °C, the speed is 350 - 400 r / min, and the reduction per single - pass rolling is 12 - 20% of the thickness of the extruded sheet.
6. The preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet according to claim 2, characterized in that, The temperature of the low - temperature aging treatment is 175 - 200 °C and the time is 8 - 16 hours.
7. The preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet according to claim 2, characterized in that, The preparation method of the magnesium alloy ingot comprises the following steps: Weigh raw materials pure magnesium ingot, pure aluminum ingot, Mg - Y master alloy, Mg - Ca master alloy and Mn source. Under a protective atmosphere, the raw materials are pre - heated and then melted, followed by refining, stirring, standing, skimming and casting to obtain the magnesium alloy ingot.
8. The preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet according to claim 7, characterized in that, The temperature of the refining is 740 - 750 °C and the time is 5 - 10 minutes.
9. The preparation method of a high-strength and high-corrosion-resistant magnesium alloy sheet according to claim 7, characterized in that, The refining agent used in the refining process comprises raw materials with the following mass fractions: KCl 49 wt%, CaCl2 24 wt%, BaCl2 14 wt%, CaF2 6 wt%, YCl3 7 wt%.
10. The preparation method of a high-strength and highly corrosion-resistant magnesium alloy sheet according to claim 2, characterized in that, The standing is as follows: First, stand at 740 - 750 °C for 30 - 40 minutes, and then cool down to 710 - 720 °C and stand for 20 - 30 minutes for iron reduction treatment.
Citation Information
Patent Citations
Low-cost high-strength anti-fatigue nonflammable wrought magnesium alloy and preparation method thereof
CN105779834A
High-flow high-corrosion-resistance magnesium alloy material and preparation method thereof
CN110629089A
High-strength and high-corrosion-resistance rare earth magnesium alloy and preparation method thereof
CN113355573A
Super-corrosion-resistant magnesium alloy and preparation method thereof
CN116987939A
Corrosion-resistant high-toughness magnesium alloy suitable for complex-structure die casting and preparation method of corrosion-resistant high-toughness magnesium alloy
CN118345290A